Prenatal Exposure to Ethanol Causes Differential Effects in Nerve Growth Factor and its Receptor in the Basal Forebrain of Preweaning and Adult Rats. (1997) - Angelucci, Francesco; Cimino, Mauro; Balduini, Walter; Piltillo, Luana; Aloe, Luigi
Abstract : In this study we investigated nerve growth factor (NGF) levels in the cortex and hippocampus of the offspring of pregnant female Sprague-Dawley rats receiving a single intragastric administration of acute ethanol on the 15th day of gestation and compared them with a control group of rats that received an injection of sucrose. We also examined the distribution of the low-affinity NGF receptor, p75NGFR, on NGF-responsive neurons that are localized in the septum and the nucleus of Meynert, which receive the respective trophic support from the hippocampus and the cortex. In the ethanol-treated group, the results show that at post-natal age 15 days, the NGF septohippocampal pathways were markedly affected. At day 15, the NGF level was significantly higher in the offspring of ethanol-treated rats. By day 40, NGF values in both groups decreased to similar levels. At day 60, however, the NGF level in the ethanol-treated animals decreased to a significantly lower value than that of the control group, which remained essentially unchanged. In parallel, at day 60 the numbers of septal cholinergic neurons expressing p75NGFR were also significantly lower in ethanol-treated rats than in control animals. Because ethanol is known to induce neurological disorders, as well as deficits in cell proliferation and differentiation, the results suggest that one cause of the deleterious effects induced by ethanol is the low availability of NGF during certain stages of postnatal brain development.